FAKTOR–FAKTOR YANG DAPAT MEMENGARUHI PENERAPAN SERTIFIKASI KEBERLANJUTAN DI KALANGAN PETANI SWADAYA DI KECAMATAN SECANGGANG - Prisman Andri Lesmana Sihombing; Maman Haeruman Karmana; Ernah Ernah (Universitas Galuh, 2022)
One of the important factors in increasing consumption of palm oil in Indonesia is because palm oil is the main ingredient for making cooking oil. The purpose of this study is to describe the factors that can affect the implementation of sustainability certification on independent smallholders in Secanggang District. The research method uses a survey. Sampling in this study uses a random sample (Random Sampling) with the number of respondents as many as 258 independent farmers. Data analysis used Binary Logistics Regression Analysis with logit regression model. The results showed that the internal factors that could influence the implementation of oil palm plantation sustainability certification among independent smallholders in Secanggang District were Farmer Age, Oil Palm Farming Experience, Number of Family Dependents and Oil Palm Farming Income, while external factors that could affect the implementation of plantation sustainability certification palm oil is Access to Information.